Enhancing Qur’an Literacy and Learning Motivation among Children in Belawan Sicanang Subdistrict - Nur Intan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe efforts to improve Qur’anic literacy and learning motivation among children in Belawan Sicanang Village. The research focuses on the condition of children’s Qur’anic literacy, the role of teachers and the environment, the strategies and methods applied, the relationship between Qur’anic literacy and learning motivation, as well as supporting and inhibiting factors. A qualitative approach was used with data collected through observation, interviews, and documentation. The results show that children’s Qur’anic literacy levels vary, depending on family support and the availability of learning facilities. Teachers play a vital role in guiding and fostering enthusiasm for learning through enjoyable and contextual approaches. Effective strategies include tahsin, talaqqi, and the use of visual and digital interactive media. Good Qur’anic literacy positively influences learning motivation by enhancing discipline, interest, and self-confidence in the learning process. The main supporting factors come from religious family and community environments, while the main obstacles are limited facilities and lack of continuous guidance.